Manganese oxide nanomaterials: bridging synthesis and therapeutic innovations for cancer treatment - Sandip Gangadhar Balwe; Dohyeon Moon; Minki Hong; Joon Myong Song (Nano Convergence)
Abstract The advent of precision medicine in oncology emphasizes the urgent need for innovative therapeutic strategies that effectively integrate diagnosis and treatment while minimizing invasiveness. Manganese oxide nanomaterials (MONs) have emerged as a promising class of nanocarriers in biomedicine, particularly for targeted drug delivery and the therapeutic management of tumors. These nanomaterials are characterized by exceptional responsiveness to the tumor microenvironment (TME), high catalytic efficiency, favorable biodegradability, and advanced capabilities in magnetic resonance imaging. These attributes significantly enhance drug delivery, facilitate real-time bioimaging, and enable early tumor detection, thereby improving the precision and effectiveness of cancer therapies. This review highlights the significant advancements in the synthesis and therapeutic applications of MONs, beginning with a comprehensive overview of key synthetic methods, including thermal decomposition, potassium permanganate reduction, exfoliation, adsorption–oxidation, and hydro/solvothermal techniques. We delve into the preparation of MONs and H–MnO₂-based nanomaterials, emphasizing their chemical properties, surface modifications, and toxicity profiles, which are critical for their clinical application. Moreover, we discuss the notable applications of H–MnO₂-based nanomaterials in pH-responsive drug release, overcoming multidrug resistance (MDR), immunotherapy, and the development of nanovaccines for synergistic cancer treatments. By addressing the current challenges in the clinical translation of MONs, we propose future research directions for overcoming these obstacles. By underscoring the potential of MONs to transform cancer treatment paradigms, this review aims to inspire further investigations into their multifunctional applications in oncology, thus ultimately contributing to more effective and personalized therapeutic strategies. Graphical abstract